Asked by | 28th Jun, 2008, 12:23: PM
We will prove the result by principle of mathematical induction.
to show, 4n -3n -1= 9(m-1), n,m N
4n -3n -1=0=9x0=9(1-1). thus, result is true for n = 1
let the result be true for n = k.
this implies, 4k-3k-1 = 9(m-1) for some m in N
consider n = k+1
=9(p-1) where p =4m+k-3 N
hence, it is true for all n in N by principle of mathematical induction.
Answered by | 15th Jul, 2008, 11:33: AM
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number